Effect of Different Types and Concentrations of Emulsifiers on the Physicochemical and Organoleptic Quality of Steamed Brownies Based on Cowpea Flour (Vigna unguiculata L.) - Isadora Harum Asta Pradika; Fadjar Kurnia Hartati; Yuyun Yuniat; Annisa Dwi Puspitarini (Demeter: Journal of Farming and Agriculture, 2025)
In order to reduce imports, diversify non-gluten products especially for celiac and autism sufferers, it is necessary to replace wheat flour, especially in making steamed brownies, including with cowpea flour. However, cowpea does not contain gluten which makes the cake elastic and soft, so it is necessary to add emulsifiers to maintain its elasticity. This study aims to determine the effect of different types and concentrations of emulsifiers on the physicochemical and organoleptic quality of brownies based on white cowpea flour and determine which composition is the best. The method used in this study is a completely randomized design (CRD) with one factor, namely the formulation of emulsifier types (J1 = SP and J2 = ovalet) and concentrations (K1 = 1% and K2 = 2%), each of which was repeated three times. The research variables observed were the analysis of the physical quality of brownies on their rising power, chemical analysis including water content, crude fiber and protein content, while the organoleptic quality analysis included tenderness, aroma, taste and color. The results showed that different types and concentrations of emulsifiers had a significant effect on water content, swelling power and tenderness. While the parameters of protein content, crude fiber, taste, color and aroma did not have a significant difference. The results showed that the best formulation was in the J2K2 treatment (Ovalet emulsifier with a concentration of 2%) with an average swelling power value of 39.42%, water content of 7.47%, crude fiber content of 3.97%, protein content of 1.21%, with an average value of organoleptic parameters of taste of 5.6 (like), aroma of 6.1 (like), tenderness of 5.53 (rather like) and color of 6.6 (very like).